Produktivitas Kata Pada Tulisan Anak Tunagrahita di Jenjang Sekolah Menengah Pertama - Rahayu Pujiastuti; Ira Eko Retnosari; Mimas Ardhianti; Indayani Indayani (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study aims to describe word productivity in the writing of children with intellectual disabilities at a lower secondary school. The research approach is both qualitative and quantitative. The data, in the form of word productivity, includes variations in word forms and the frequency of word types in the writing of five children with mild intellectual disabilities, who served as the data sources for this study. Data collection utilised testing and documentation techniques. The data collection instruments comprised verbal and visual media as well as questions. The data collection procedure involved (1) determining the data collection pattern, (2) conducting tests, (3) collecting documents in the form of the children’s writing, and (4) validating the data. Data analysis employed the distribution method. The data analysis instruments consisted of tables to reduce the data so that each data unit, the overall data, and the relationships between aspects could be observed. The data analysis procedures were carried out by (1) reducing the data, (2) presenting the data, (3) interpreting the data, (4) drawing conclusions, and (5) validating the findings. Data validity was ensured through the triangulation of theory, method, and sources. The research findings concern the lexical productivity in the writing of children with mild intellectual disabilities, based on variations in word forms, including root words, affixed words, and reduplication. Root words are highly dominant. Eight-word classes were identified: nouns, verbs, adjectives, adverbs, numerals, pronouns, prepositions, and conjunctions, whilst interjections, articles, and particles were not found. Nouns, verbs, and adjectives occur frequently. This information indicates that the development of word productivity in children with mild intellectual disabilities at the lower secondary school level still reflects a mastery of simple linguistic structures and concrete word types rather than complex morphological structures and abstract word types. Abstrak Penelitian ini bertujuan untuk mendeskripsikan produktivitas kata dalam tulisan anak tunagrahita di SMP. Pendekatan penelitian ini adalah kualitatif dan kuantitatif. Data berupa produktivitas kata, meliputi variasi bentuk kata dan frekuensi jenis kata pada tulisan lima anak tunagrahita ringan yang menjadi sumber data penelitian ini. Pengumpulan data menggunakan teknik tes dan dokumentasi. Instrumen pengumpulan data berupa media verbal dan visual serta soal. Prosedur pengumpulan data dilakukan dengan (1) menentukan pola pengumpulan data, (2) melakukan tes, (3) mengumpulkan dokumen berupa tulisan anak, dan (4) mengabsahkan data. Penganalisisan data menggunakan metode agih. Instrumen penganalisisan data berupa tabel untuk mereduksi data agar dapat melihat setiap satuan data, data keseluruhan, dan hubungan antaraspek. Prosedur penganalisisan data dilakukan dengan (1) mereduksi data, (2) menyajikan data, (3) menginterpretasi data, (4) menyimpulkan, dan (5) mengabsahkan temuan. Keabsahan data menggunakan triangulasi teori, metode, dan sumber. Hasil penelitian berupa produktivitas kata pada tulisan anak tunagrahita berdasarkan variasi bentuk kata, meliputi kata dasar, kata berafiks, dan reduplikasi. Kata dasar sangat dominan. Delapan jenis kata yang ditemukan, yaitu nomina, verba, adjektiva, adverbia, numeralia, pronominal, preposisi, dan konjungsi, sedangkan interjeksi, artikula, dan partikel belum ditemukan. Jenis kata nomina, verba, dan adjektiva memiliki frekuensi yang tinggi. Informasi ini menjelaskan bahwa perkembangan produktivitas kata anak tunagrahita ringan di SMP masih menggambarkan penguasaan struktur bahasa yang sederhana dan jenis kata yang konkrit daripada struktur morfologis yang kompleks dan jenis kata yang abstrak.